Teachers’ Experiences in Flipped Classroom in South-East Asian Countries: A Meta-Synthesis - Jr, Angelito Cabanilla; Pogoy, Angeline (FKIP Universitas Lampung, 2023)
Teachers’ Experiences in Flipped Classroom in South-East Asian Countries: A Meta-Synthesis. This study aimed to meta-synthesize the teachers' experiences utilizing flipped classrooms across South-East Asian countries. Fifteen (15) out of 1,118 studies were included from various accessible academic databases in Publish or Perish software which was scrutinized using a set of inclusion and exclusion criteria. The included studies were organized using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 flow diagram, and were analyzed using Braun and Clarke's six-step thematic analysis, which generated five themes and one meta-theme. This meta-synthesis revealed that teachers utilizing flipped classrooms experienced varied experiences from shifting roles, making them more efficient, and improved teacher-student interaction. Teachers also experienced anxieties and faced challenges, yet no studies from the fifteen studies have shown how to address the said challenges. It is recommended that Teacher Education Institutions provide comprehensive training on appropriate technology and emotional and psychological support for the teachers utilizing flipped classrooms. Keywords: flipped classroom, teachers’ experiences, meta-synthesis, south-east asia, systematic review.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202306